Criminal Policy as an Effort to Overcome Defamation Crimes on Social Networks (Research in the Jurisdiction of the North Sumatra Regional Police) - Duha, Wiraswan; Zulyadi, Rizkan; Frensh, Wenggedes (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of information technology, especially in the realm of computers, has created a significant impact on security in cyberspace, including increasing cases of cyber crimes such as defamation. This article analyzes the laws related to defamation in social networks based on the ITE Law. This research uses normative and empirical juridical approaches to highlight weaknesses in policy implementation, such as ambiguous definitions and differences in interpretation between the ITE Law and the Criminal Code. In addition, the article proposes non-penal policy alternatives, such as religious and moral approaches, in addressing cybercrime. However, obstacles such as the lack of public understanding of the ITE Law and limited infrastructure and human resources in the police cyber unit were also identified. By understanding these challenges, it is hoped that law enforcement against cybercrime can be improved to create a safer and more ethical cyber environment.